The influence of stressor on blood pressure in school children - Sudung O Pardede; Partini P Trihono; Irene Yuniar; Taralan Tambunan (Indonesian Pediatric Society Publishing House, 2016)
Background Physical and psychological stress such as child anxi- ety, can increase blood pressure. Objective To evaluate the role of vein puncture as a stressor caus- ing alteration of blood pressure in school children. Methods This study was a descriptive, pre and post test study as a part of a screening study on primary school children at Cibubur subdistrict in East Jakarta. Blood pressure was measured before and after a vein puncture procedure in 449 children. Nine children were excluded because of incomplete data. Results The increase of systolic blood pressure was found in 121 (27.5%) subjects, decrease in 42 (9.5%), and no change in 227 (63%). Diastolic blood pressure increased in 123 (28.0%) subjects, decreased in 38 (8.6%), and did not change in 279 (63.4%). The increase of both systolic and diastolic blood pressure was found in 61 (13.8%), increased systolic with no change of diastolic in 58 (13.2%), and increased systolic with decreased diastolic in 2 (0.5%) children. Decreased systolic with increased diastolic was found in 2 (0.5%) subjects, decreased systolic with no change of diastolic in 26 (5.9%), and decrease of both systolic and diastolic in 14 (3.2%) children. No changes in both systolic and diastolic blood pressure were found in 195 (44.3%); no change in systolic with decreased diastolic blood pressure was found in 22 (5.0%) children. Conclusion In most of the school children, vein puncture proce- dure did not cause alteration on blood pressure